Urban sustainability, agglomeration forces and the technological deus ex machina - Peter Nijkamp; Erik Teodoor Verhoef (European Regional Science Association (ERSA), 2001)
This paper addresses the issue of spatial environmental externalities from a spatial general equilibrium perspective. We present a general equilibrium model of an island economy, with one city and a rural hinterland. Apart from market-internal interactions such as those governing trade and locational choice, the small economy considered encompasses a number of spatial external effects. Agglomeration externalities explain why industrial production is concentrated in a city, where land prices are higher than elsewhere. Industrial production however leads to environmental pollution, which negatively affects the quality of life within the city and rural agricultural production elsewhere. The paper explores the welfare properties of market-based spatial general equilibria compared to efficient configurations. The conclusions allow a welfare economic assessment of the currently popular concept of `ecological footprints' from a spatial general equilibrium viewpoint.
Keywords: 330